Correction: Mapping the Distribution of Anthrax in Mainland China, 2005-2013. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2016)
[This corrects the article DOI: 10.1371/journal.pntd.0004637.].